The synthesis of substituted phosphathiahelicenes via regioselective bromination of a preformed helical scaffold: a new approach to modular ligands for enantioselective gold-catalysis. Issue 73 (18th August 2016) - Aillard, Paul; Dova, Davide; Magné, Valentin; Retailleau, Pascal; Cauteruccio, Silvia; Licandro, Emanuela; Voituriez, Arnaud; Marinetti, Angela
Abstract : New substituted phosphathiahelicenes have been synthesized and used as ligands in gold(i )-catalyzed [4+2] cyclizations of 1, 6-enynes (up to 91% ee). Abstract : Substituted phosphathiahelicenes have been prepared via a straightforward two-step procedure involving the regioselective bromination of a preformed helical scaffold, followed by palladium catalyzed coupling reactions. The new helicenes have been used as ligands in gold(i )-catalyzed [4+2] cyclizations of 1, 6-enynes. The resulting dihydro-cyclopenta[ b ]naphthalene derivative was obtained in excellent yields and with up to 91% ee.